NEW HETEROCYCLIC COMPOUNDS WITH AN OXADIAZOLE MOIETY SYNTHESISED AND EVALUATED TABS (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
Developing a new medication is called drug discovery in medicine and pharmacology. The active ingredient of a medication may have been discovered by coincidence, or it may have been identified in traditional treatments. The use of heterocyclic molecule analogues in biology has attracted a lot of attention in recent years. Ox diazoles have antibacterial, antiviral and fungicidal, anti-cancer and inflammatory properties. They also have an anti-hypertensive and an anti-conversant action. Efforts to assemble published data on the varied pharmacological activities of ox diazole derivatives and any further endeavors in this field were the goal of this study. Ox diazole derivatives have been shown to have several biological effects in the scientific literature, which is the topic of this study.
Keywords: Heterocyclic compounds; oxadiazoles